IMF Survey, Volume 35, Issue 04. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2006)
IMF strategic review; IMF transparency report; Article IV summaries: Mauritius, Zambia, Guinea; South Asia and oil prices; New EU member experiences with capital account opening; AFRITACS future work plan; Goldsbrough on FSAP; global imbalances.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet